Visum et Repertum as criminal evidence within the Indonesian criminal justice system - Tohom Hasiholan; Abdul Madjid; Nurini Aprilianda; Adi Kusumaningrum (International Review of Social Sciences Research)
This research discusses the use of Visum et Repertum (VeR), an expert testimony, as evidence in criminal justice system in Indonesia. The main issue identified in this research is the legal vacuum regarding the use of VeR before the investigation, which results in VeR made during the preliminary investigation stage not having the same legal force as VeR made during the investigation stage. Hence, this study used normative legal approach with analysis of applicable legislation. The analysis shows that VeR has a strong legal position as valid evidence according to the Criminal Procedure Code but there is an urgent need for regulations that state VeR requested during the preliminary investigation stage can be used as evidence with the same probative force as VeR requested during the investigation stage. This study proposes the issuance of regulations stating that VeR made before the investigation remains valid, both investigators and interrogators are authorized to request VeR in writing, and the probative force of VeR requested during the preliminary investigation stage should be considered equivalent to VeR requested during the investigation stage.